(untitled) (Indian Journal of Animal Production and Management, 2017)
A holistic farming system is the need of the hour as the vital resources like land, water; credit and marketing are becoming scarcer. An integrated farming consists of a range of resource saving practices that aim to achieve acceptable profits and high and sustained production levels, while minimizing the negative effects of intensive farming and preserving the environment. Proper utilization of cow dung and urine into manure, vermin-compost pesticides, ayurvedic preparations etc can not only generate income but also protect the soil from fertilizers and chemicals besides harnessing the energy and fuel needs of the rural India. Scientific studies on socio economic impact of different farming systems by the researchers of various disciplines of sciences is needed to arrive at a broad based agriculture system aiming at the nutritional security of the small, marginal and landless farm families.